La Pianificazione Comunale per il rischio incendi di interfaccia - Soddu, PierLuigi; Cavarra, Luciano; Losavio, Giacomo; Torrisi, Antonio (GEOmedia, 2008)
Municipality planning for urban/forest interface fires risk Brush fires constantly torment Italy, especially during summer times. In this context the italian Department of Civil Protection (DPC) aims to coordinate the various entities implied on the field in order to safeguard and protect citizens and private-public real estates from this kind of dangers. To do that the DPC leans on new technologies like GIS and on a wide organizational structure that also comprises the municipalities.